Pelatihan Mengajar Metode Iqra’ untuk Anggota Muslimat Nahdlatul Ulama Kecamatan Tempuling Kabupaten Indragiri Hilir - Kafrawi Kafrawi; Mulyadi Mulyadi (STAI Auliaurrasyidin Tembilahan, 2020)
One of the efforts of Al-Qur'an teachers attempted to find is the best method for teaching the Quran. They, the teachers wish that the Quran can be delivered and read easily for anyone. So, the Iqra method is an effort to make the Quran easier to learn and read it accurately. This method is important for teachers, groups of ta'lim who teach the Qur'an because it directly teaches the tajwid in some stages. However, it is also important to deliver these community activities for Muslim members, especially NU (Nahdatul Ulama) where most of its members are majlis ta'lim and teachers of the (TPA). The purpose of this community service was to give an understanding of teaching this method. This activity successfully achieved two goals. 1. Internal targets: NU Muslims can deliver better teaching method than their previous teaching. 2. External targets: They experienced in teaching the Iqra method. The strategy or the method used during this community service was questioning, and answers to the participants.